Epigenetic alterations of CYLD promoter modulate its expression in gastric adenocarcinoma: A footprint of infections. Issue 4 (21st August 2018) - Ghadami, Elham; Nikbakhsh, Novin; Fattahi, Sadegh; Kosari‐Monfared, Mohadeseh; Ranaee, Mohammad; Taheri, Hassan; Amjadi‐Moheb, Fatemeh; Godazandeh, Gholamali; Shafaei, Shahryar; Nosrati, Anahita; Pilehchian Langroudi, Maryam; Samadani, Ali Akbar; et al.
Abstract: Gastric cancer (GC) is one of the most common causes of cancer‐related death in the world, with multiple genetic and epigenetic alterations involved in disease development. CYLD tumor suppressor gene encodes a multifunctional deubiquitinase which negatively regulates various signaling pathways. Deregulation of this gene has been found in different types of cancer. This study aimed to evaluate for the first time the CpG island methylation pattern of CYLD gene promoter, and its expression level in gastric adenocarcinoma. CYLD messenger RNA expression and promoter methylation in 53 tumoral and their non‐neoplastic counterpart tissues were assessed using quantitative polymerase chain reaction and bisulfite sequencing. Also, we investigated the impacts of the infectious agents including Helicobacter pylori ( H. pylori ), EBV, and CMV on CYLD expression and promoter methylation in GC. Results showed that the expression level of CYLD was downregulated in GC, and was significantly associated with gender (female), patient's age (<60), high grade, and no lymph‐node metastasis ( p  = 0.001, 0.002, 0.03, and 0.003, respectively). Among the 31 analyzed CpG sites located in about 600 bp region within the promoter, two CpG sites were hypermethylated in GC tissues. We also found a significant inverse association between DNA promoter methylation and CYLD expression ( p  = 0.02). Furthermore, a direct association between H . pylori, EBV, and CMV infections with hypermethylation and reduced CYLD expression was observed ( p  = 0.04, 0.03, and 0.03, respectively). Our findings indicate that CYLD is downregulated in GC. Infectious agents may influence CYLD expression. Abstract : CYLD is a tumor suppressor gene which negatively regulates various signaling pathways. Infections may cause epigenetic modifications that affect CYLD gene expression in gastric cancer.